Investigation of an outbreak of acute diarrheal disease in Dibrugarh district, Assam, India, 2023 - Roopa Hariprasad; Pranjal Jyoti Baruah; Muthusamy Santhosh Kumar; Pallab Sarmah; Tulika Goswami Mahanta; Tarun Bhatnagar (Elsevier, 2024)
Background: On January 30, 2023, 26 acute diarrheal disease (ADD) cases and a death were reported from a village in Dibrugarh, Assam, India. We investigated and described the outbreak by time, place and person, identified the potential exposures, and formulated recommendations. Methods: We defined a case of ADD as the occurrence of loose stools (≥3 episodes) between January 27, 2023 and February 11, 2023. We conducted a door-to-door case search, calculated attack rates by age and gender, drew an epidemic curve, and plotted cases by residence. We performed a case-control study to identify possible exposure variables, calculated odds ratio (OR) with 95 % confidence interval (CI), and collected stool and water specimens from households and schools for laboratory testing. Results: We identified a total of 55 cases, with an overall attack rate of 5.6 % and one death (case fatality rate of 1.8 %). School-going children exhibited a higher attack rate of 39 %. Shigella flexneri was isolated from one of the stool specimens. Furthermore, the water obtained from households' tube wells exceeded the permissible limits of E. coli for consumption. Consuming prasadam (Sacred food) at a school religious event (OR = 6.2, 95 % CI = 2.6-15.2) and not washing hands after defecation (OR = 8.2, 95 % CI = 1.7-38) were associated with ADD. Conclusion: The results indicated that the food served during the school religious event could potentially be the source of the ADD outbreak. The food served during the event likely acted as a medium for community transmission, possibly due to unhygienic practices and contaminated drinking water.